THE IMPACT OF THE COVID-19 PANDEMIC ON HOSPITALIZATIONS AND ADMISSION PROFILE OF PATIENTS WITH HEART FAILURE DECOMPENSATION AT THE ALBERT EINSTEIN ISRAELITA HOSPITAL - Rampazo Prado, Elisa (Health and Society, 2024)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic was officially declared by the WHO on March 11, 2020, and the first Brazilian case was registered on February 26, 2020. Since then, health systems have been adapted to receive the emerging flow of patients requiring hospitalization due to moderate to severe manifestations of COVID-19 infection. In this scenario, patients with chronic comorbidities were advised to stay at home, as a way to minimize the chances of infection. Thus, the current context determined that patients who presented decompensated Heart Failure (HF) had their medical-hospital care altered, a fact already evidenced by an English study from June 2020, which observed a reduction in the number of hospitalizations during the pandemic due to exacerbation of HF and a worse clinical profile at the time of hospital admission2. In this sense, a reduction in the number of hospitalizations due to HF decompensation was observed at Hospital Israelita Albert Einstein (HIAE) from March to August 2020. In this study, we will evaluate the impact of the COVID-19 pandemic on hospitalizations due to HF decompensation at HIAE, through data on the clinical profile at the time of admission and the evolution of these patients during hospitalization, comparing them with the period before the pandemic by the new coronavirus. Objective: The objectives of the present study aim to quantify the reduction in hospitalizations, evaluate the clinical profile at the time of admission and evaluate the morbidity and mortality of these patients, comparing the current pandemic data with previous data. We do not aim to analyze the relationship between COVID-19 infection and cardiovascular disease. Methods: Retrospective observational cohort study, carried out in a database of patients who were admitted to HIAE with decompensated Heart Failure, between the periods of October 2019 and August 2020. Inclusion criteria were patients with reduced left ventricular ejection fraction (LVEF ≤ 45%) and age ≥ 18 years. Patients were not tested for COVID-19 diagnosis. The sample was characterized based on the mean and standard deviation, minimum and maximum, median and quartiles, for quantitative variables, and by absolute and relative frequencies, for qualitative variables. Comparisons between periods were verified using Chi-square or Fisher’s exact tests, and Student’s t-tests or Mann-Whitney tests, according to the distribution characteristic. Data normality was verified using the Shapiro-Wilk test, bloxplot graphs, histograms and quantile comparison graphs. Results: During the pandemic period, we saw an increase in the number of hospitalizations due to decompensated heart failure, with these patients being more severe, with rising creatinine levels during hospitalization and higher mortality due to HF during the pandemic. However, these patients admitted to the service had a higher ejection fraction compared to the previous period. The use of vasoconstrictor and inotropic drugs remained the same. We had more female hospitalizations when compared to the pre-pandemic period. Conclusion: The number of hospitalizations due to acute HF did not decrease during the pandemic period, which differs from previous literature. However, we corroborate the idea that there is an increase in severity and morbidity of hospitalized patients. More female patients were hospitalized, and the hospitalized patients had a higher LVEF compared to the pre-pandemic period.